2019
DOI: 10.1039/c9ra06445a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of growth kinetics of CO2 hydrates and multiphase flow properties of slurries in high pressure flow systems

Abstract: The formation and accumulation of hydrates in high pressure oil and gas pipelines bring great risks to field development and deep-water transportation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
1
23
1
Order By: Relevance
“…Contrary to this result in the present study, Lv et al. , reported that the hydrate formation in the later stage is inhibited at a higher water flow rate because the gas‐liquid interface is covered by the formed hydrate, by promotion of the mass transfer. In this study, the decreasing trend of the hydrate formation rate was not observed.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to this result in the present study, Lv et al. , reported that the hydrate formation in the later stage is inhibited at a higher water flow rate because the gas‐liquid interface is covered by the formed hydrate, by promotion of the mass transfer. In this study, the decreasing trend of the hydrate formation rate was not observed.…”
Section: Resultscontrasting
confidence: 99%
“…Lv et al 15 explored the influence of the amount of liquid transferred in a pure water system on the induction time of hydrate formation in an experiment on the influencing factors of hydrate formation characteristics and found that the hydrate induction time first decreased and then increased with the increase in the carrier liquid with the V-type tendency, which is in good agreement with the results of this experiment. The amount of carrier liquid in the pure water system and the water content in the oil−water emulsion system directly affected the size of the gas−water interface area, which determined the formation of hydrates and the distribution state and volume fraction of hydrates in the system.…”
Section: Results and Analysismentioning
confidence: 99%
“…Most scholars use single-factor methods to conduct qualitative research on these factors, , such as the effects of pressure, temperature, water content, and additives on the induction time of hydrate formation; however, there is a lack of sensitivity analysis on the degree of influence of various factors on the induction time of hydrate formation. The theoretical basis of the degree of sensitivity analysis is as follows: ,, the dependent variable Y is affected by the independent variables X 1 , X 2 , X 3 , ..., X m . A total of n experiments were performed as follows: where X ik represents the value of the independent variable X of the k th test, and Y k represents the value of the dependent variable Y of the k th test.…”
Section: Sensitivity Analysis Of Factors Affecting Hydrate Induction ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the growth process and growth rate of hydrates in pipelines has found that the main reason hydrates form blockages in pipelines is that they adhere to the pipelines due to the formation of a liquid bridge . Reducing the adhesion of hydrates is one of the effective ways to solve the blockages that they form.…”
Section: Introductionmentioning
confidence: 99%